Understanding structure-property relationships in coordination polymers: a comparative study of the copper() and zinc() coordination mechanism - Benekou, Vasiliki; Zhang, Zhe; Sporrer, Lukas; Candini, Andrea; Monti, Filippo; Kovtun, Alessandro; Liscio, Fabiola; Mannsfeld, Stefan C. B; Feng, Xinliang; Dong, Renhao; Palermo, Vincenzo (Nanoscale, 2025)
Coordination polymers (CPs) are an interesting class of materials due to their tunable structures and electrical properties where, however, the correlation between the former and latter is still not fully understood. Here we compare the structures and properties of CPs derived from copper( ii ) and zinc( ii ) ions coordinating a triphenylene derivative (OHPTP). To focus on the effect of the coordinating ion used and avoid possible differences due to the processing method, we synthesized different CPs using a novel two-step technique, potentially scalable for applications in transistors, sensors, and photovoltaics: first, the organic ligand is deposited using a shear-coating technique which ensures uniform deposition on the macroscopic scale. Then, in the second step, the sample is exposed to solutions of the metal ions, which can penetrate in the organic layer to coordinate with the ligand. Density functional theory (DFT) calculations show that Cu ions have a higher affinity for the ligand and form square-planar CP structures due to their d 9 electronic configuration. Conversely, Zn ions can coordinate with the chelating ligands using only their empty 4s and 4p orbitals to achieve sp 3 hybridisation, thus preferring to adopt a tetrahedral geometry and leading to less ordered structures with significantly hampered conductivity. FT-IR and UV-vis spectra, XPS and conductive atomic force microscopy confirm the distinct coordination behaviour of Cu and Zn ions. Thermal stability analysis further shows that Zn-based CPs retain their structural integrity at temperatures up to 300 °C, whereas Cu-based CPs degrade earlier. These results show how metal-ligand interactions impact the properties of CPs, enhancing the understanding of structure-property relationships, and provide practical insights for designing CPs with desired electronic and thermal properties by varying the coordinating metal ions. In metal-organic coordination polymers, metal ions can adopt square-planar or tetrahedral geometries, affecting electronic properties. These configurations are studied via AFM, XPS, and DFT modelling to compare structural and electronic differences.